Child Sleep Coaches: Current State and Future Directions. (January 2017) - Mindell, Jodi A.; Owens, Judith A.; Babcock, Debra; Crabtree, Valerie McLaughlin; Ingram, David
Given the genuine gaps in the availability of clinical sleep services for children, sleep coaching as a field has emerged and appears to be significantly increasing. Sleep coaches are typically individuals who provide individualized services, often via the Internet or phone, to families of infants and young children (and increasingly to older children, adolescents, and adults as well) with sleep problems. At this time, there is no universally accepted definition of sleep coach, nor are there clear guidelines regarding educational background, training requirements, scope of practice, or credentialing. To start to address the needs of families seeking the services of a sleep coach, educational materials were developed for parents and health care providers regarding issues to consider. Furthermore, there is a need going forward that (1) the designation sleep coach or consultant be clear and well defined, with a clear standard of care and scope of practice; (2) there is a standard core body of knowledge included in all training programs; (3) a certification process is developed for sleep coaches that is reputable and has recognizable and clear standards; and (4) that care for sleep problems in infants and young children are available to diverse populations, irrespective of socioeconomic status.